A drift of Langmuir waves in a magnetized inhomogeneous plasma. (February 2019) - Erofeev, Vasily I.
Abstract : The concept of informativeness of nonlinear plasma physics scenarios is explained. Natural ideas of developing highly informative models of plasma kinetics are spelled out. They are applied to develop a formula that governs the drift of long Langmuir waves in spatial positions and wave vectors in a magnetized plasma due to the plasma inhomogeneity. Together with previous findings (Erofeev, Phys. Plasmas, vol. 22, 2015, 092302), the formula evidences the need for an intelligent generalization of the notion of wave energy density from usual homogeneous plasmas to inhomogeneous ones.